RETRENCHING EMPLOYEES IN STAGES TO CIRCUMVENT SECTION 189A OF THE LRA NUMSA v Continental Tyre (as yet unreported – Labour Court 2005) - Adriaan van der Walt; Glynis van der Walt (Obiter, 2022)
As a result of pressure from the trade union movement to reconsider the policy norms governing retrenchments, significant amendments, both procedural and substantive, were made to the retrenchment provisions in the Labour Relations Act, 1995 (“the LRA”) in 2002. A new section (s 189A) was introduced which provides that where a potential retrenchment involves at least 10 employees where an employer employs has more than 50 employees such employees acquire the right to strike in opposition to the retrenchment. Employees and trade unions can elect to challenge such retrenchment through the law or by means of protected strike action (see s 65(4)(c)). Section 189A(1)(a) provides that this section applies to employers employing more than 50 employees if – “(a) the employer contemplates dismissing by reason of the employer’s operational requirements, at least – (i) 10 employees, if the employer employs up to 200 employees; (ii) 20 employees, if the employer employs more than 200, but not more than 300, employees; (iii) 30 employees, if the employer employs more than 300, but not more than 400, employees; (iv) 40 employee employees, if the employer employs more than 400, but not more than 500, employees; or (v) 50 employee employees, if the employer employs more than 500, employees.” An additional consequence of the introduction of section 189A is that provision is made for statutory facilitation in respect of the retrenchment consultation at the request of the employer or any consulting parties representing the majority of employees who are targeted for retrenchment. Compulsory notice periods are also introduced, since the section requires a 60 day holding-off period if statutory facilitation is embarked upon or pending terminations disputed (s 189A(2)(a) read with s 189A(7)(a) and 189A(8)(b)(i); and see Thompson “Restructuring and Retrenchment” 2002 Current Labour Law 30). In order to prevent employers from circumventing the effect of section 189A by splitting or staggering a retrenchment, section 189A provides that, if the number of employees that an employer contemplates dismissing, together with the number of employees that have been dismissed by reason of that employer’s operational requirements in the 12 months prior to the employer issuing a retrenchment notice, is equal to or exceeds the relevant number set out above the section applies to the second retrenchment exercise as well (s 189A(1)(b)). This provision is important, because the additional rights granted to employees and trade unions by section 189A are significant (as set out above). But what if an employer retrenches employees in an instance where section 189A does not apply, and thereafter retrenches more employees within the following 12 months or even later? Should section 189A apply to the first retrenchment which, on its own, falls short of the numbers that cause the section to apply? This issue was recently addressed in NUMSA v Continental Tyre (unreported – Labour Court 2005).